Ignoring the sacroiliac joint in chronic low back pain is costly [Corrigendum] - Polly DW; Cher D (Dove Medical Press, 2016)
Polly DW, Cher D. Clinicoecon Outcomes Res. 2016;8:23–31.The authors would like to make a correction to the Disclosure statement. The corrected statement is as follows:David Polly is an investigator in clinical research studies sponsored by SI-BONE but has no financial interest in the company. Daniel Cher is an SI-BONE employee. SI-BONE sponsored the clinical trial from which data were used in the reported model. SI-BONE manufactures the implant used in the SIJF surgery studied. The authors report no other conflicts of interest in this work.Read the original article